(untitled) (Journal of Oriental Studies, 2016)
Modern foreign philosophers continue to explore creativity al-Farabi. At the same time, scientists of Muslim origin are found in his writings support the basic doctrines of the religion of Islam. They believe that now in the modern world, the scope and intensity of intellectual challenges are much greater than those faced by our medieval ancestors, but this only further underscores the need to base all efforts on the principle of distinction between good and evil, essential and secondary, from these positions need to study such a prominent figure as al-Farabi, whose works can be considered as a supplement to the sources of the Islamic revelation. For philosophers of the European tradition and innovation, the importance of al-Farabi is seen in the fact that he represents a multitude of nations of the world "fused" together in a single political organization under the guidance of a wise ruler, or that al-Farabi led to the first interpenetration - Arabism in Hellenism and Hellenism in Arabism. Highly appreciated the fact that al-Farabi had a great influence on medieval thinkers of Europe.